Appropriate technology of pediatric emergency medicine - Zhu Lihui Zhu Yimin; Wang Li Luo Haiyan (China : Editorial Board Member, 2016)
Pediatric emergency (intensive care) room is an important place dedicated to the intensive care and rescue of critically ill children in a hospital.
Table of Contents Chapter I Appropriate technologies of pediatric emergency treatment for country-level medical institutions Sections 1 Standarization of pediatric emergency (intensive care) Rooms Section 2 Transfer in pediatri emergency treatment Section 3 Application of scoring critical pediatric cases Section 4 Introduction and treatment of pediatric acute heart failure Section 5 Pediatric encephaledemea and intracranial hypertension syndrome Section 6 Treatmen of shock for children Section 7 Drowing Section 8 Application of noninvasive ventilation CPAC for children Chapter II Management for pediatric emergency in rural hospital Section 1 Febrile convulsion Section 2 Pneumonia in children Section 3 Oxygen therapy Section 4 Dehydration and liquid therapy for children Section 5 Antimicrobial agents application of children community-acquired infection Section 6 Management of fever in infarts and children Section 7 Diarrhea diasease and use of oral rehydratation salts Appendix
Incluye Table of contents
Incluye Table of Appendix
Keywords: PEDIATRICS -- EMERGENCY; PEDIATRÍA -- EMERGENCIAS